Interrelationship Of Thread Deformation And Structure - Shokir A. Abdulazizov; Khusankhon T. Bobojanov; Sabirjon A. Yusupov; Akhtam A. Qosimov (Genius Journals, 2024)
In this article, the relationship between yarn deformation and the structure of textile and light industrial products was studied. The theoretical and experimental foundations of the mechanics of the stretching deformation of textile threads, and the study of test conditions taking into account the linear density of the semi-finished product are covered. The purpose of these practical tests is to determine the zones of elastic and plastic deformations of the threads and the numerical values of the change in the deformation of the thread at the same moment when the load is applied and removed
Keywords: Semi-periodic deformation; one-periodic deformation; experimental